A Combined (U‐Th)/He and Cosmogenic 3He Record of Landscape Armoring by Biogeochemical Iron Cycling. Issue 2 (20th February 2018) - Monteiro, H. S.; Vasconcelos, P. M. P.; Farley, K. A.
Abstract: (U‐Th)/He geochronology and cosmogenic 3 He in iron oxides reveal mineral precipitation ages as old as 55 Ma and exposure ages greater than 5 Ma for canga‐cemented plateaus in the Quadrilátero Ferrífero, Brazil, showing that lateritic profiles overlying banded iron‐formation (BIF) landscapes in tropical regions have a long history of surface exposure. The long‐term erosion history obtained from cosmogenic 3 He on BIF plateaus confirms that relic surfaces persist in the landscape for millions of years. Combined 3 He and (U‐Th)/He dating shows that cangas are preferentially goethite cemented by biogeochemical reactions in the subsurface. Importantly, pebbles of hematite‐magnetite in colluvia or shallow creeks draining the canga‐cemented plateaus record a much longer exposure history than in situ canga blocks, showing that even older duricrusts, now eroded, once blanketed these plateaus. Physically stable but biogeochemically dynamic, cangas armor the landscape by pervasive and recurrent iron cycling and cementation, slowing down the delivery of weathered BIF or friable hematite–magnetite ore to erosion. Key Points: We combine (U‐Th)/He dating and cosmogenic 3 He measurements in supergene iron oxides to study relic banded iron‐formation (BIF) landscapes We confirm that cangas are long‐lasting features that armor the landscape and slow the delivery of weathered BIF to erosion Precipitation of goethite cements takes place primarily in the subsurface